Eram realmente pitagórico(a)s os homens e mulheres catalogado(a)s por Jâmblico em sua obra Vida de Pitágoras? - Silva, Josildo Jose Barbosa da (2010)
Pythagoras was one of the most important pre-Socratic thinkers, and the movement he founded, Pythagoreanism, influenced a whole thought later in religion and science. Iamblichus, an important Neoplatonic and Neopythagorean philosopher of the third century AD, produced one of the most important biographies of Pythagoras in his work Life of Pythagoras. In it he portrays the life of Pythagoras and provides information on Pythagoreanism, such as the Pythagorean religious community which resembled the cult of mysteries; the Pythagorean involvement in political affairs and in the government in southern Italy, the use of music by the Pythagoreans (means of purification of healing, use of theoretical study), the Pythagorean ethic (Pythagorean friendship and loyalty, temperance, self-control, inner balance); justice; and the attack on the Pythagoreans. Also in this biography, Iamblichus, almost seven hundred years after the termination of the Pythagorean School, established a catalog list with the names of two hundred and eighteen men and sixteen women, supposedly Pythagoreans of different nationalities. Based on this biography, a question was raised: to what extent and in what ways, can the Pythagoreans quoted by Iamblichus really be classified as Pythagoreans? We will take as guiding elements to search for answers to our central problem the following general objectives: to identify, whenever possible, which of the men and women listed in the Iamblichus catalog may be deemed Pythagorean and specific; (a) to describe the mystery religions; (b) to reflect on the similarities between the cult of mysteries and the Pythagorean School; (c) to develop criteria to define what is being a Pythagorean; (d) to define a Pythagorean; (e) to identify, if possible, through names, places of birth, life, thoughts, work, lifestyle, generation, etc.., each of the men and women listed by Iamblichus; (f) to highlight who, in the catalog, could really be considered Pythagorean, or adjusting to one or more criteria established in c, or also to the provisions of item d. To realize these goals, we conducted a literature review based on ancient sources that discuss the Pythagoreanism, especially Iamblichus (1986), Plato (2000), Aristotle (2009), as well as modern scholars of the Pythagorean movement, Cameron (1938), Burnet (1955), Burkert (1972), Barnes (1997), Gorman (n.d.), Guthrie (1988), Khan (1999), Mattéi (2000), Kirk, Raven and Shofield (2005), Fossa and Gorman (n.d.) (2010). The results of our survey show that, despite little or no availability of information on the names of alleged Pythagoreans listed by Iamblichus, if we apply the criteria and the definition set by us of what comes to be a Pythagorean to some names for which we have evidence, it is possible to assume that Iamblichus produced a list which included some Pythagoreans